2019
DOI: 10.1016/j.metop.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diet, lifestyle and psychological factors in the prognosis of ischemic heart failure

Abstract: Background/Objective Dietary patterns may play an important role in the prognosis of heart failure. Methods Dietary habits, sleeping habits, physical activity and anxiety and depression status were recorded in 326 patients (90 females, mean age 73.45 ± 10.9 years) with ischemic heart failure prospectively followed for 30 months. Results Lower ΗADS-depression scores (p = 0.03), a low-fat meat diet (p = 0.035) and moderate coffee consumption (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Elderly age could also play a role in cluster 4. In cluster 3, two important factors could be the high percentages of males and the frequency of unhealthy lifestyles known to be important risk factors for cardiac diseases [44].…”
Section: Discussionmentioning
confidence: 99%
“…Elderly age could also play a role in cluster 4. In cluster 3, two important factors could be the high percentages of males and the frequency of unhealthy lifestyles known to be important risk factors for cardiac diseases [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies identified the association of napping practice with incidence and prevalence of MetS, and type 2 DM [ [29] , [30] , [31] ]. In contrast, midday nap is not associated with the prognosis of ischemic heart failure [ 32 ]. While there is a consistent U-shaped curve association between short (<6 h) and long (>8 h) nocturnal sleep with ill health, daytime napping with short duration of nighttime sleep has been connected with an increased risk of developing type 2 DM.…”
Section: Discussionmentioning
confidence: 99%